Synthesis of Semantic Model of Subject Area at Integration of Relational Databases - Filatov, V.; Semenets, V.; Zolotukhin, O. (My University, 2019)
The article considers the problem of synthesizing a semantic model of the subject area at integration of heterogeneous information resources. In this case, emphasis is placed on ensuring the universality of the means of description, without regard to artificial limitations on the data typification and categorization. Two types of logical existence rules are introduced: functional and structural ones, which allow analyzing not only explicitly defined, but also logically deducible information objects, that is, determining the boundary of the subject area. Information about all possible information objects of the subject area makes it possible to determine the area of intersection of the ntegrable data semantics.
Keywords: reengineering; relational database; data semantics; subject area; data integration; data model